EFL Students’ Perceptions on the Use of Quillbot Paraphrasing Tool in Essay Writing - Nuraeni, Ayu; Febriani, R. Bunga; Rustandi, Andi (Universitas Galuh, 2025)
This research discusses about EFL Students’ Perceptions On The Use Of Quillbot Paraphrasing Tool In Essay Writing. The objective of this study was aimed to elaborate on how EFL students implement the QuillBot Paraphrasing Tool in essay writing and EFL students perceive of use the QuillBot Paraphrasing Tool in essay writing. This study used a descriptive qualitative method, involved 25 students’ of English Education who used QuillBot Paraphrasing Tool In Essay Writing. Brief rating scales questionnaires were used to gather the data. The results showed that students responded positively to the use of the QuiillBot Paraphrasing Tool In Essay Writing. Most students agree that using QuillBot makes the process of paraphrasing in writing easier and more efficient. QuillBot can help students paraphrase and avoid plagiarism in their writing. While this tool is powerful, Quillbot may be a useful tool for EFL students, but it's important to remember that it shouldn't be overly relied on. Students should continue to concentrate on improving their paraphrasing skills while using Quillbot to complement their endeavors and students should use it wisely. The researcher suggests that future researchers are expected to be able to examine more sources and references related to paraphrasing using QuillBot.